2021
DOI: 10.1111/anu.13378
|View full text |Cite
|
Sign up to set email alerts
|

Effects of tributyrin on growth performance, immune response and intestinal barrier function of juvenile grass carp ( Ctenopharyngodon idellus ) fed diets with high cottonseed and rapeseed meal

Abstract: Tributyrin (TB) has applications as a growth and intestinal health promoter for animals. A 10-week feeding trial was conducted to evaluate the application of TB to relieve the negative effects induced by high cottonseed and rapeseed meal (CRM) in juvenile grass carp (Ctenopharyngodon idellus; initial weight 9.59 ± 0.01 g). Grass carp were fed a normal fish meal (FM) diet (positive control [PC], 50 g/kg FM, 340 g/ kg CRM), high CRM diet (T0, 20 g/kg FM, 540 g/kg CRM) or a T0 diet supplemented with 500 (T500), 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 58 publications
0
3
0
Order By: Relevance
“…Glycerol tributanoate can be hydrolyzed to produce glycerol and butyric acid, which can be metabolized through nutrition and provide energy for small intestinal epithelial cells 68 , 69 . Glycerol tributanoate can increase the ATP content, activate PIK3 and AKT signal transduction, further activate important Nrf2 signal pathways in cells, enhance the expression of antioxidant enzyme genes, and thus enhance antioxidant enzyme activity 70 . Therefore, the high level of Glycerol tributanoate in Lv-T shrimp may provide energy to resist cold stress and enhance antioxidant capacity.…”
Section: Discussionmentioning
confidence: 99%
“…Glycerol tributanoate can be hydrolyzed to produce glycerol and butyric acid, which can be metabolized through nutrition and provide energy for small intestinal epithelial cells 68 , 69 . Glycerol tributanoate can increase the ATP content, activate PIK3 and AKT signal transduction, further activate important Nrf2 signal pathways in cells, enhance the expression of antioxidant enzyme genes, and thus enhance antioxidant enzyme activity 70 . Therefore, the high level of Glycerol tributanoate in Lv-T shrimp may provide energy to resist cold stress and enhance antioxidant capacity.…”
Section: Discussionmentioning
confidence: 99%
“…The authors suggested 0.10% TB supplementation as the optimal percentage to maximise growth in grass carp-fed diets with high cottonseed and rapeseed meal. 118…”
Section: Tributyrin Supplementation In Omnivorous and Herbivorous Fis...mentioning
confidence: 99%
“…The immunity indices were also similar between the positive control group and the groups supplemented with 0.10% and 0.15% TB. The authors suggested 0.10% TB supplementation as the optimal percentage to maximise growth in grass carp‐fed diets with high cottonseed and rapeseed meal 118 …”
Section: Tributyrin—characterisation and Potential Applicationsmentioning
confidence: 99%